REGULATORY SUPPORT AND THE FUNCTIONALITY OF THE SYSTEM INFORMATION MONITORING THE SAFETY OF OPERATIONS IN AVIATION - G. E. Glukhov; I. G. Kirpichev; P. E. Chernikov (Научный вестник МГТУ ГА)
The analysis has been made of documents currently in force in the Russian Federation to regulate the state meosures to implement the USOAP CMA. The model of dtate information system is developed the safety of the procedures in aviation Suggestions are given on the set of functions carried by the system and on the functions performed by the system participants.